Biochar as a novel technology for treatment of onsite domestic wastewater: A critical review - Muoghalu, Chimdi C.; Owusu, Prosper Achaw; Lebu, Sarah; Nakagiri, Anne; Semiyaga, Swaib; Iorhemen, Oliver Terna; Manga, Musa (Frontiers in Environmental Science, 2023)
Globally, about 2.7 billion people depend on onsite sanitation systems (OSS) (e.g., septic tanks) for their sanitation needs. Although OSS help in providing primary treatment for domestic wastewater, they don’t effectively remove nutrients, pathogens, and other inorganic contaminants. Previous studies have posited that the use of post-treatment systems which incorporate biochar leads to improved contaminant removal efficiency. However, the mechanism through which contaminants are removed and factors potentially affecting the removal are still understudied. To fill this knowledge gaps, this review discusses factors which affect efficiency of biochar in removing contaminants found in onsite domestic wastewater, modifications applied to improve the efficiency of biochar in removing contaminants, mechanisms through which different contaminants are removed and constraints in the use of biochar for onsite wastewater treatment. It was noted that the removal of contaminants involves a combination of mechanisms which include adsorption, filtration, biodegradation, ion exchange, and pore entrapment. The combination of these mechanisms is brought about by the synergy between the properties of biochar and microbes trapped in the biofilm on the surface of the biochar. Future areas of research such as the modification of biochar and the use of biochar in the removal of antimicrobial-resistant genes (ARGs) are also discussed. This study provides useful information that can be applied in the use of biochar for the treatment of wastewater and guide the future design of treatment systems for optimized treatment performance.